RANKL Blockade Reduces Cachexia and Bone Loss Induced by Non‐Metastatic Ovarian Cancer in Mice - Pin, Fabrizio; Jones, Alexander J; Huot, Joshua R; Narasimhan, Ashok; Zimmers, Teresa A; Bonewald, Lynda F; Bonetto, Andrea (Journal of bone and mineral research, 2022)
ABSTRACT Tumor‐ and bone‐derived soluble factors have been proposed to participate in the alterations of skeletal muscle size and function in cachexia. We previously showed that mice bearing ovarian cancer (OvCa) exhibit cachexia associated with marked bone loss, whereas bone‐targeting agents, such as bisphosphonates, are able to preserve muscle mass in animals exposed to anticancer drugs. De‐identified CT images and plasma samples from female patients affected with OvCa were used for body composition assessment and quantification of circulating cross‐linked C‐telopeptide type I (CTX‐I) and receptor activator of NF‐kB ligand (RANKL), respectively. Female mice bearing ES‐2 tumors were used to characterize cancer‐ and RANKL‐associated effects on muscle and bone. Murine C2C12 and human HSMM myotube cultures were used to determine the OvCa‐ and RANKL‐dependent effects on myofiber size. To the extent of isolating new regulators of bone and muscle in cachexia, here we demonstrate that subjects affected with OvCa display evidence of cachexia and increased bone turnover. Similarly, mice carrying OvCa present high RANKL levels. By using in vitro and in vivo experimental models, we found that elevated circulating RANKL is sufficient to cause skeletal muscle atrophy and bone resorption, whereas bone preservation by means of antiresorptive and anti‐RANKL treatments concurrently benefit muscle mass and function in cancer cachexia. Altogether, our data contribute to identifying RANKL as a novel therapeutic target for the treatment of musculoskeletal complications associated with RANKL‐expressing non‐metastatic cancers. © 2021 American Society for Bone and Mineral Research (ASBMR). RANKL directly impairs muscle mass and function in cancer cachexia. Tumor‐derived factors, including RANKL, drive bone resorption in non‐bone metastatic cancer. Blockade of RANKL and cancer‐associated bone resorption results in improved muscle mass and function, even in the absence of bone metastases.